Fiqh Mu' asarah and bioethics: A comparative analysis of Islamic and western / Nur Shahida Mohamed … [et al.] - Mohamed, Nur Shahida; Azhan, Siti Khairul Aisyah; Mohd Ali, Nursyahida; Patul Muin, Fairuz Irdina; Azman, Norshahira (2023)
In general, Islam encourages the use of science, medicine, and biotechnology as a solution to human suffering. So, it cannot be denied that Muslims worldwide may be eager to use the latest medical developments. However, we cannot ignore Western bioethics which also attracts the attention of today's society. There is a difference between Western bioethics and Islamic bioethics. Therefore, there are several issues that need to be addressed in this study about bioethics issues in treatment such as test tubes and renting a womb, and what is the role of Mu'asarah jurisprudence in solving these issues. There are also three objectives that are also studied in this study, namely, about the issues involving bioethics in treatment and the role of Fiqh Mu'asarah in solving these issues, understanding in detail the concept of Fiqh Mu'asarah and the meaning of bioethics, and knowing details on the differences between western and Islamic bioethics. In order to achieve the three objectives, qualitative methods are used to obtain accurate reference sources such as primary data and secondary data. The conclusion of this study, in general, it can be said that this study sheds light on the roots of the four principles in Islamic teachings and elaborates on the differences between Western and contemporary Islamic bioethics.